The Educational Meaning of Fasting in the Integration of Islamic Education, Health, and Psychological Self Regulation - Muh Habibulloh (CV. Agrapana Media, 2026)
Fasting is one of the acts of worship in Islam that not only has a spiritual dimension but also contains educational values that contribute to character development, health, and the development of psychological self-regulation. This study aims to analyze the educational meaning of fasting from the perspective of Islamic education and to explain its contribution to physical health, mental health, and the strengthening of an individual's psychological self-regulation. This study uses a qualitative approach with a library research design. Data were obtained through a review of various literature sources, including scientific books, national and international journal articles, and academic documents relevant to the topics of fasting, Islamic education, health, and psychology. The data collection technique was carried out through documentation studies, while data analysis used content analysis techniques which include the processes of data reduction, data presentation, and systematic drawing of conclusions. The results of the study indicate that fasting contains educational values such as patience, discipline, self-control, social empathy, and spiritual awareness, which can be integrated into the Islamic education process. These values contribute to character formation, strengthening psychological self-regulation abilities, as well as developing a healthier lifestyle both physically and mentally. The integration of fasting values in Islamic education can be an effective learning strategy in shaping individuals who have a balance between spiritual, health, and self-control dimensions. Therefore, fasting is not only understood as a ritual worship practice, but also as an educational process that has broad implications for improving the quality of life.